EFFECTIVENESS OF COMMUNITY COLLABORATION AGENCIES IN TACKLING DISCIPLINE ISSUES IN PUBLIC SECONDARY SCHOOLS IN TARIME DISTRICT COUNCIL, TANZANIA - Paul, Joseph; Mkulu, Demetria Gerold; Mwila, Prospery M (International Journal For Research In Educational Studies, 2023)
Community collaboration agencies are the major school stakeholders in managing discipline issues. To promote discipline in a given school, community collaboration agencies (CCAs) must become heavily involved in school-related matters such as discipline. However, the extent of being involved in matters concerning discipline is not promising due to the increasing discipline issues that occur every now and then in public secondary schools. Consequently, the study sought to explore the extent of community collaboration agency involvement in tackling discipline issues in public secondary schools in the Tarime District Council, Tanzania. The study was guided by the McGregory Theory of X and Y of 1960, employing a mixed research approach and an explanatory sequential mixed design. Data were gathered using questionnaires, interview guides and document analysis. The study involved a target population of 7412, in which a sample size of 209 participants was selected, including 98 students and 78 teachers selected through simple random sampling, 24 parents, 4 heads of schools, 4 ward education officers, and a district secondary education officer. Content and face validity were verified to determine the validity of the research tools. The questionnaires achieved a correlation coefficient of 0.734, which disclosed the high reliability of the research tools. Quantitative data were analysed by using descriptive statistics with SPSS version 23, and qualitative data were analysed thematically via narrations and direct quotations. The results revealed that CCAs are not doing enough to solve discipline issues in public secondary school in the Tarime district council. The study recommended that the government should revise the curriculum, education acts and policies governing discipline issues and see the need to implement the parent-teacher association. The CCAs should work together to create good relationships by allowing maximum cooperation with each other.